Calculated bets : computers, gambling, and mathematical modeling to win - Steven S Skiena (Cambridge ; New York : Cambridge University Press, 2001)
This is a book about a gambling system that works. The author tells the story of how he used computer simulations and mathematical modeling techniques to predict the outcome of jai-alai matches and bet on them successfully - increasing his initial stake by over 500% in one year!
Keywords: Mathematical models; Gambling -- Mathematical models